Physiological and molecular insights into the resilience of biological nitrogen fixation to applied nitrogen in Saccharum spontaneum, wild progenitor of sugarcane - Luo, Ting; Li, Chang-Ning; Yan, Rui; Huang, Kejun; Li, Yang-Rui; Liu, Xiao-Yan; Lakshmanan, Prakash (Frontiers in Plant Science, 2023)
Excessive use of nitrogen (N) fertilizer for sugarcane cultivation is a significant cause of greenhouse gas emission. N use-efficiency (NUE) of sugarcane is relatively low, and considerable effort is now directed to exploit biological nitrogen fixation (BNF) in sugarcane. We hypothesize that genetic base-broadening of sugarcane using high-BNF Saccharum spontaneum, a wild progenitor of sugarcane, will help develop N-efficient varieties. We found remarkable genetic variation for BNF and growth in S. spontaneum accessions, and BNF in some accessions remained highly resilient to inorganic N application. Physiological and molecular analyses of two S. spontaneum accessions with high-BNF capacity and growth, namely G152 and G3, grown under N replete and low N conditions showed considerable similarity for total N, NH4-N, soluble sugar, indoleacetic acid, gibberellic acid, zeatin and abscisic acid content; yet, they were strikingly different at molecular level. Global gene expression analysis of G152 and G3 grown under contrasting N supply showed genotype effect explaining much of the gene expression variation observed. Differential gene expression analysis found an over-representation of carbohydrate and amino acid metabolism and transmembrane transport genes in G152 and an enrichment of lipid metabolism and single-organism processes genes in G3, suggesting that distinctly divergent metabolic strategies are driving N-related processes in these accessions. This was attested by the remarkable variation in carbon, N, amino acid and hormone metabolism-related gene expression in G152 and G3 under high- and low-N supply. We conclude that both accessions may be achieving similar BNF and growth phenotypes through overlapping but distinctly different biochemical and molecular mechanisms.